2004
DOI: 10.1182/blood-2004-01-0380
|View full text |Cite
|
Sign up to set email alerts
|

NK cell activation by dendritic cells (DCs) requires the formation of a synapse leading to IL-12 polarization in DCs

Abstract: Mature dendritic cells (mDCs) can trigger the effector functions of natural killer (NK) cells. Knockout , small-interfering RNA or neutralizing antibodies targeting interleukin 12 (IL-12) subunits revealed a critical role for IL-12 in NK cell interferon (IFN-) secretion promoted by mDCs. However, NK cell activation by DCs also required direct cell-to-cell contacts. DC-mediated NK cell activation involved the formation of stimulatory synapses between DCs and NK cells. The formation of DC/NK cell conjugates depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
284
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(300 citation statements)
references
References 47 publications
(64 reference statements)
14
284
1
1
Order By: Relevance
“…This phenomenon was observed in both autologous and Killer cell Immunoglobulinlike Receptor mismatched NK-DC cocultures. Ligation of NK-cell receptors could be responsible for this contact dependency [15]; however, the formation of an immunological synapse could also be an important factor [39]. Next to IL-18, other possible candidates are MICA/B [15] and in trans presented IL-15 [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was observed in both autologous and Killer cell Immunoglobulinlike Receptor mismatched NK-DC cocultures. Ligation of NK-cell receptors could be responsible for this contact dependency [15]; however, the formation of an immunological synapse could also be an important factor [39]. Next to IL-18, other possible candidates are MICA/B [15] and in trans presented IL-15 [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the observed changes are most probably the result of synergistic effects mediated by diverse activating cytokines. In this regard, IL-12 was also detected in sera after αGalCerMPEG stimulation and might be relevant for NKT-cell-induced NK-cell differentiation and functionality [42].…”
Section: Uneducated and Educated Nk Cells Are Crucial Players For Virmentioning
confidence: 99%
“…Therefore, the observed changes are most probably the result of synergistic effects mediated by diverse activating cytokines. In this regard, IL-12 was also detected in sera after αGalCerMPEG stimulation and might be relevant for NKT-cell-induced NK-cell differentiation and functionality [42].The transcriptional pathways leading to NK-cell activation are mainly mediated by the transcription factors Eomes and T-bet via . The observed NKT-cellmediated increase in the expression of Eomes might contribute to explain the enhanced secretion of IFNÎł.…”
mentioning
confidence: 99%
“…2-4 More recently, Borg et al reported that DC-mediated NK cell activation required the formation of a synapse, which led to IL-12 polarization in DC. 5 In addition to the DC to NK cell contact-dependent mechanism, IL-12 or IFNs secreted from DC are also involved in initiating the activation of NK cells.It has been reported that precursor DC have the ability to produce type1 IFNs,6 and that precursor DC activated by viral infection are induced to increase the production of type1 IFNs, which activate NK cells. 7 CD40L is essential for the activation of DC, followed by the induction of cytokine production.…”
mentioning
confidence: 99%
“…[2][3][4] More recently, Borg et al reported that DC-mediated NK cell activation required the formation of a synapse, which led to IL-12 polarization in DC. 5 In addition to the DC to NK cell contact-dependent mechanism, IL-12 or IFNs secreted from DC are also involved in initiating the activation of NK cells.…”
mentioning
confidence: 99%